ECOPEDAGOGY-BASED ISLAMIC EDUCATION MANAGEMENT, CULTURAL INTEGRATION OF GRASTONOMI GALENDO IN LOCAL HISTORY LEARNING AT RIYADLUL ULUM TASIKMALAYA UNIVERSITY - Syarif Hidayat (Program Studi Manajemen Pendidikan Islam, 2026)
This research is motivated by the urgency of integrating ecological values into curriculum management and local history education as a manifestation of the human ethical responsibility as khalifah fil ardh (stewards of the earth). The purpose of this study is to analyze the phenomenon of integrating ecological issues through the Cultural Ecology Learning Model (MPEB) based on Islamic Education Management in the Local History course at Universitas Riyadlul Ulum Tasikmalaya, as well as its impact on historical tourism in Ciamis. This research employs a qualitative approach with a case study method to explore the complexity of policy implementation. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed using triangulation techniques and the analysis model by Creswell (2014). The results indicate that the integration of Galendo-based gastronomy in MPEB successfully constructed a transformative historical understanding, shifting the anthropocentric paradigm to an ecocentric one through the MERDEKA pathway. The study concludes that MPEB serves as an effective Islamic Education Management framework for integrating local history as a research basis for contemporary ecological problem-solving and green economy empowerment in alignment with rahmatan lil alamin values